Enhancing Organizational Performance Through Service Quality and Customer Satisfaction in Competitive Business Environments - Afzal Sayed Munna; Andhi Febisatria; Giuseppe Umberto Cantafio (International Journal of Educational Administration, Management, and Leadership, 2025)
In increasingly competitive business environments, service quality has become a strategic capability that enables organizations to satisfy customers and improve organizational performance. This study examines the direct effect of service quality on organizational performance and the indirect effect through the mediating role of customer satisfaction. The study is grounded in the Expectation–Disconfirmation Theory (EDT) and the Resource-Based View (RBV), which explain how superior service quality creates positive customer evaluations that ultimately contribute to sustainable organizational performance. A quantitative research approach was employed using a cross-sectional survey design. Data were collected from 152 employees working in service-oriented organizations across the retail, hospitality, financial services, healthcare, and telecommunications sectors in Indonesia. The research utilized Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4 as the analytical tool to evaluate both the measurement and structural models. The findings indicate that service quality has a positive and significant effect on customer satisfaction and organizational performance. Customer satisfaction also exerts a positive and significant influence on organizational performance and partially mediates the relationship between service quality and organizational performance. These findings demonstrate that organizations achieve superior performance not only by delivering high-quality services but also by ensuring that customers perceive and experience those services positively. This study contributes to the service management literature by providing empirical evidence that customer satisfaction serves as a critical mechanism through which service quality is translated into organizational performance, offering practical implications for managers seeking to strengthen organizational competitiveness through customer-centered service strategies.